Imbangan Paitan (Tithonia diversifolia) dan Pupuk Phonska terhadap Kandungan Logam Berat Cr pada Tanah Sawah - Sri Hartati; Jauhari Syamsiah; Elen Erniasita (Faculty of Agriculture, Universitas Sebelas Maret, 2014)
TITLE : RATIO OF PAITAN (TITHONIA DIVERSIFOLIA) AND THE PHONSKA FERTILIZER ON CHROMIUM HEAVY METAL CONTENT IN THE RICE FIELDS. The purposes of this research are to determine the influence of Paitan (Tithonia diversifolia) and the Phonska Fertilizer on Chromium (Cr) Content in soil at rice fields; and the correlation between Cr and rice yield. This research was conducted in Kebakkramat District, Karanganyar Regency. The experiment was arranged using Randomized Completely Block Design (RCBD), with 6 (six) treatments included: T0 : control (without Paitan nor fertilizer), T1: Phonska 100% (360 kg/ha), T2 : Paitan 100% (11,66 ton/ha), T3: 75% Phonska + 25% Paitan, T4 : 50% Phonska + 50% Paitan, T5 : 25% Phonska +75% paitan. with 4 replications. The observed variables are soil Cr availability, dry biomass, and the weight of 1000 seeds, The data was analyzed using the F test of 1% and 5% levels, and DMRT was employed to investigate the interaction of each treatment. The Pearson’s correlation test was used to investigate the correlation between variables. The results showed that application of paitan (Tithonia diversifolia) and Phonska gave no significant effect to the Cr level. There was no significant correlation between Cr level and the yield of rice.